Evaluating Cardinal temperature for seed germination rate of Salvia spp - سارا طهماسبی گوجگی; حسنعلی نقدی بادی; علی مهرآفرین; وحید عبدوسی; محمدرضا لبافی (علوم و فناوری بذر ایران, 2014)
Evaluating of an appropriate model is critical for quantifying the response of germination rate to temperature and determination of cardinal temperatures. This study was conducted to evaluate different nonlinear regression models to describe response of germination rate to temperature in Salvia species. The regression models were dent-like, segmented and beta. Root mean squareof error, coefficient of determination, correlation coefficient and regression of predicted values versus observed ones were used to find the appropriate model(s). Dent-like and segment models were superior compared to the Beta model in Salvia species. It was concluded that these models can be used to quantify response of Salvia species germination to temperature and to obtain cardinal temperature of germination. These parameters are required to predict Salvia species germination and emergence.